Christliches Gebet-Buch auf all Tage in der Wochen zu gebrauchen - Habermann, Johann 1516-1590 (Berlin Lorentz, 1712)
Habermann's prayer book apportioned for the first time the prayers for various Christian needs among the several days of the week. With a few exceptions the prayers are written in plain Biblical language, without ornament. The work was translated into Latin, English (as The Enimie of Securitie, London, 1580), and French, and was widely circulated in Protestant circles. Despite its occasional crudities of expression the book is still used; and some of the prayers have passed into church books.
Habermann was a Lutheran theologian, edification writer and Hebraist
Bound in with Crüger's 'Praxis pietatis melica'
Originally published in 1565 as 'Christliche Gebet für alle Not und Stende der gantzen Christenheit'
Ex libris Frederikke Tuxen (plate)
Marbled end papers, gilt gauffered edges, metal locks
Am Ende ist auch ein schöner und nötiger Unterricht für diejenigen so zum Tische des Herrn gehen wollen nebst denen dazu gehörigen Gebeten mit hinangefüget: Darauf folgen dan weiter die drey haupt-Symbola zusamt einigen schönen anderen mehren Krancken- und Starb-Gebetlein wie imgleichen vielen schönen Trost- Kraft- und Kern-Sprüchen. Nach verschiedenen andern Editionen übersehen und an vielen Orten wieder ersetzet.
Keywords: 17th Century (1601-1700); 18th Century (1701-1800); Prayer; Lutheranism; Germany